Fragile X-Associated Tremor Ataxia Syndrome in FMR1 Gray Zone Allele Carriers - Hall, Deborah (Mov Disord, 2011)
PURPOSE: Carriers of fragile X mental retardation 1 (FMR1) repeat expansions in the premutation range (55–200 CGG repeats) often develop a syndrome of kinetic tremor, cerebellar ataxia, and parkinsonism; designated the fragile X-associated tremor ataxia syndrome (FXTAS). Neurological signs have not been reported in carriers of gray zone (45–54 CGG repeats) expansions. METHODS/RESULTS: We describe three patients with FMR1 gray zone alleles who meet diagnostic criteria for FXTAS. CONCLUSIONS: Our cases suggest that the definition of the FXTAS may need to be broadened to include individuals with FMR1 repeat expansions in the gray zone. These neurological signs may be due to elevated levels of expanded CGG repeat FMR1 mRNA in the gray zone carriers, similar to the changes seen in premutation carriers with FXTAS.